Seberapa Efisien Penggunaan Aplikasi E-Commerce dalam Mempengaruhi Keputusan Pembelian: Studi Kasus Pada Aplikasi Klik Indomaret - Bahtiar, Dandi; Marlina, Nanan (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
Online sales have increased for several years, so retail companies need to change their sales strategy from offline to online sales, PT. Indomarco Prismatama, was launching the Klik Indomaret application. This study aims to see how much influence the Klik Indomaret application proxied with E-Commerce Application Variables has on the Purchase Decision Variable. The Personal Selling variable is used as a control variable in this study. Analysis using Regression with JAMOVI application. This study also uses a descriptive analysis approach. The samples that were collected were 270 visitors by systematic random sampling. The findings show that the Klik Indomaret Application affects the Purchase Decision Variable with a significance number below 5%, namely 0.001 and has the ability to predict 97.5%. As for the Personal Selling Control Variable, the effect is 90.9%. The results of the descriptive analysis, it was found that the skills and